A Tillage-Dependent System of Arable Pests: How Soil Condition and Prevailing Climate Influence Pest Occurrence? - Sándor Keszthelyi; Zoltán Tóth; Adalbert Balog (Agronomy, 2025)
Conventional and conservation tillage systems are applied differently in agricultural practices. Considering the current trends, the spread of tillage before denser crop cultures can also be observed in the case of other crops. These systems alter microclimatic conditions in the cultivated layer, soil surface, and crop canopy by physically modifying the soil environment. This greatly influences the occurrence and success of microbiome, plant, and animal organisms. At the same time, it has a decisive influence on the occurrence and damage caused to crops by harmful microorganisms and herbivorous pests. This review investigates how tillage systems influence the emergence and mass propagation of herbivores, based on their soil dependency. The impact of soil as a medium on pests will be analysed by grouping them according to their soil attachment and providing cultivation and agro-zoological examples. We highlight that selecting a tillage system should consider soil-dwelling pest ecology, as this knowledge is critical for optimizing both soil health and crop protection.